Augmented Endoscopy for Surveillance of Colonic Inflammatory Bowel Disease: Systematic Review With Network Meta-analysis. (28th December 2018) - Imperatore, Nicola; Castiglione, Fabiana; Testa, Anna; De Palma, Giovanni Domenico; Caporaso, Nicola; Cassese, Gianluca; Rispo, Antonio
Abstract: Introduction: Considering the high risk of dysplasia and cancer in inflammatory bowel disease [IBD], surveillance is advocated. However, international guidelines do not reach a uniform recommendation on the way to perform surveillance. We performed a systematic review with a meta-analysis to assess the best endoscopic surveillance strategy in colonic IBD. Methods: The systematic review was performed in PubMed/MEDLINE, EMBASE, SCOPUS, and Cochrane databases to identify studies comparing white light endoscopy [WLE] and augmented endoscopy [AE] in the detection of dysplasia/neoplasia in colonic IBD. A sub-analysis between dye-spray chromoendoscopy [DCE], narrow-band imaging [NBI], I-SCAN, full-spectrum endoscopy [FUSE], and auto-fluorescence imaging [AFI] was also performed. Furthermore, a meta-regression and a network meta-analysis were also performed. Results: A total of 27 studies [6167 IBD patients with 2024 dysplastic lesions] met the inclusion criteria. There was no publication bias. AE showed a higher likelihood of detecting dysplasia than WLE (19.3% vs 8.5%, odds ratio [OR] = 2.036), with an incremental yield [IY] of 10.8%. DCE [OR = 2.605] and AFI [OR = 3.055] had higher likelihood of detecting dysplasia than WLE; otherwise, I-SCAN [OR = 1.096], NBI [OR = 0.650], and FUSE [OR = 1.118] were not superior to WLE. Dysplasia was found in 1256/7267 targeted biopsies [17.3%] and in 363/110 040 random biopsies [0.33%] [OR = 66.559, IY = 16.9%]. Meta-regression found no variable impacting on the efficacy of AE techniques. Network meta-analysis identified a significant superiority of DCE to WLE in detecting dysplasia [OR 2.12], but no other single technique was found to be superior to all others in dysplasia detection. Conclusions: DCE was associated with higher likelihood of discovering dysplastic lesions than WLE. Chromoendoscopy is the best supported endoscopic technique for IBD surveillance.